Facilitators and Barriers to Breastfeeding and Exclusive Breastfeeding in Kilimanjaro Region, Tanzania: A Qualitative Study - Melina Mgongo; Tamara H. Hussein; Babill Stray-Pedersen; Siri Vangen; Sia E. Msuya; Margareta Wandel (International Journal of Pediatrics)
Background. Breastfeeding is the best way to feed infants. It is a simple intervention to improve child health and development. Despite its advantages, there is a low global rate of exclusive breastfeeding (EBF) and, in Kilimanjaro region, Tanzania, EBF is rarely practiced. The aim of this paper is to explore social and cultural factors that might influence the practice of breastfeeding and exclusive breastfeeding in Kilimanjaro region. Methods. A qualitative design was used. Three districts in Kilimanjaro region, namely, Same, Moshi Municipal Council, and Rombo, were selected. In each district three focus group discussions (FGDs) were conducted with mothers with infants aged 0-12 months. Results. A total of 78 mothers participated in the focus group discussions. A majority of the mothers were positive towards breastfeeding. They believed that it prevents child sickness, creates happiness, and is good for family economy. Despite the positive attitudes, the mothers revealed many perceptions that interfered with breastfeeding and exclusive breastfeeding. These included the following: breast milk is very light and has bad odor, breastfeeding may affect mothers appearance, chango (abdominal pain) has to be treated, there is fear of the evil eye when breastfeeding in public places, breast milk may become unclean, and there is a need of pauses in breastfeeding after the child has burped on the breast. Conclusion. There are beliefs that promote the practice of breastfeeding in this setting; these local beliefs could be used to develop breastfeeding messages to improve breastfeeding practices. However, there is also a need to address beliefs that interfere with the practice of exclusive breastfeeding in this setting.